Why Are Adult Women Missing? Son Preference and Maternal Survival in India - Milazzo, Annamaria (World Bank, Washington, DC, 2014)
This paper is the first to show that excess mortality among adult women can be partly explained by strong preference for male children, the same cultural norm widely known to cause excess mortality before birth or at young ages. Using pooled individual-level data for India, the paper compares the age structure and anemia status of women by the sex of their first-born and uncovers several new findings. First, the share of living women with a first-born girl is a decreasing function of the women's age at the time of the survey. Second, while there are no systematic differences at the time of birth, women with a first-born girl are significantly more likely to develop anemia when young (under the age of 30) and these differences disappear for older women. Moreover, among those in the older age group, they appear to be significantly better off in terms of various predetermined characteristics. These findings are consistent with a selection effect in which maternal and adult mortality is higher for women with first-born girls, especially the poor and uneducated with limited access to health care and prenatal sex diagnostic technologies. To ensure the desired sex composition of children, these women resort to a fertility behavior medically known to increase their risk of death. The observed sex ratios for first births imply that 2.2-8.4 percent of women with first-born girls are 'missing' because of son preference between the ages of 30 and 49.